Survei Kondisi Fisik Atlet Pencak Silat Persaudaraan Setia Hati Terate - Arifin, Agus Zaenal; Amiq, Fahrial; Fitriady, Gema (Universitas Negeri Malang, 2020)
This study aims to determine the physical condition of the athletes of the UKM PSHT UM pencak silat. The physical components measured were arm muscle strength, abdominal muscle strength, leg muscle strength, agility, and cardiovascular endurance. The research method used is descriptive quantitative research method with survey technique design. The subjects in this study were 27 athletes of the UKM PSHT UM pencak silat, consisting of 21 male athletes and 6 female athletes. The results of the physical condition of the male athletes obtained arm muscle strength in the